Odpowiedź :
2x-3) ² + (x-4) ² - 4x² + 10x- 16 =4x²-12x+9+x²-8x+16-4x²+10x-16=x²-10x+9
(2x-3)² + (x-4)²- 4x² + 10x- 16=
= (2x)²+ 3²- (2•2x•3)+ x² + 4²- (2•4•x)-4x² +10x- 16=
= 4x² + 9- 12x+ x²+ 16- 8x- 4x²+ 10x- 16=
= 9+x²-12x- 8x+10x=
= 9+ x²- 10x=
= x²- 10x +9
tak to wygląda po przekształceniu na funkcję kwadratową, bo musi być:
y= ax²+bx+c
i masz już uporządkowane ;)
= (2x)²+ 3²- (2•2x•3)+ x² + 4²- (2•4•x)-4x² +10x- 16=
= 4x² + 9- 12x+ x²+ 16- 8x- 4x²+ 10x- 16=
= 9+x²-12x- 8x+10x=
= 9+ x²- 10x=
= x²- 10x +9
tak to wygląda po przekształceniu na funkcję kwadratową, bo musi być:
y= ax²+bx+c
i masz już uporządkowane ;)
(2x-3)²+(x-4)²-4x²+10x-16=4x²-12x+9+x²-8x+16-4x²+10x-16=x²-10x+9